The Future of Health Care in the Kurdistan Region-Iraq Toward an Effective, High-Quality System with an Emphasis on Primary Care - Moore, Melinda (RAND Corporation, 2014)
Presents the results of a yearlong analysis of the health care system in the Kurdistan Region of Iraq, with a focus on primary care. The authors project future supply and demand for health services, describe the strengths of the health care system in the Kurdistan Region as well as the challenges it faces including financing issues, and discusses what strategies can be pursued to move toward a more effective and higher-quality health care system.